Rare but real: Takotsubo syndrome following mitral valve surgery. Issue 3 (6th February 2020) - Totaro, Pasquale; Triolo, Oreste F.; Argano, Vincenzo
Abstract: Background: Takotsubo syndrome has been widely recognized as a stress cardiomyopathy and only recently has been also reported following cardiac surgery. Aims: We present a case of takotsubo syndrome two days following a mitral valve replacement with a mechanical prosthesis. Materials and Methods: A 64‐year‐old female patient underwent mitral valve replacement with a mechanical prosthesis. Two days later she presented clinical symptoms and diagnostic evidence supporting the diagnosis of takotsubo syndrome. Results: Patient underwent full left ventricle function recovery and was discharged home on 10th postoperative days. Discussion: The peculiar aspect of this case consist of the early postoperative transthoracic echocardiography, which showed, clearly, an optimal left ventricle function the day before sudden onset of the symptoms, thus allowing for a clear differential diagnosis with other potential causes of postoperative left ventricle failure. Conclusion: This case confirms that takotsubo syndrome has to be carefully considered in differential diagnosis in case of acute left ventricle dysfunction following cardiac surgery.